Short-term natural restoration effects on groundwater table in several peatland conditions of Acacia plantation forests - Qalbi, Andria Harfani; Tarigan, Suria Darma; Barus, Baba; Sudadi , Untung (Journal of Degraded and Mining Lands Management, 2025)
One significant approach to restore the ecosystem function of degraded peatlands is natural restoration. This study evaluated the effect of short-term natural restoration on groundwater table in several peatland conditions in the Acacia plantation retired since 2016. Four types of land: burned land, Acacia post-harvest land, retired Acacia plantation forest, and the natural forest were considered as our study area. This study analyzed soil properties and remote sensing using the NDVI index to evaluate vegetation density in 2016, 2019, and 2022. This study found that natural restoration in the period of 2016-2022 increased vegetation density, almost similar to natural forest vegetation. Both soil properties and groundwater table on Acacia plantation forest and natural forest were not significantly different. High saturated hydraulic conductivity and low bulk density on both areas supported the stability of peat hydrology. In addition, variations in rainfall affected the pattern of changes in groundwater table, with a decrease during the dry season and an increase during the rainy season. The findings of this study confirm that short-term natural restoration can restore hydrological and vegetation functions in degraded peatlands, especially in Acacia plantation areas. These findings can be scientific recommendations for sustainable peatland management.